Technology and young children : A review of literature - Alexandra E. Appel; D Chloe O’Gara (Tech-KnowLogia, 2001)
Interest in using personal computer technology as an instructional medium with young children is growing around the world. Many parents, teachers, and even national governments2 are convinced that early interaction with technology stimulates learning and gives children a head start on success in the technological world of the future. This article reviews current research on developmental issues and the use of technology in learning environments for 4, 5 and 6-year-old preschool children. The reviewers are cognizant of the controversy revolving around whether the developmental needs of children are best met when technology is introduced into the learning environment. However, since that technology is now prevalent in the social contexts of many young children, tracking best practice guidelines for the introduction of technology into early learning environments is a necessity for early childhood development professionals and educators. The goal of this brief review is to inquire how current practices address developmentally appropriate learning, and to review guidance on how best to use computers with young children.
Keywords: apprentissage; écriture et lecture numériques; jeunesse